Investigation of a soil stratification upper section by rapid methods of wave analysis - Antipov Vadim Valer’evich (Vestnik MGSU, 2016)
This article presents the comparative results of an investigation of the low-velocity zone of the area near the housing of the PNRPU engineering faculty by active and passive methods of multichannel analysis of surface waves (MASW). MASW is a modern nondestructive method researching the soil massif. It lets to obtain profiles of transverse velocities and to find initial elastic modulus and initial shear modulus by using these profiles. The purpose of the investigation is a study of low-velocity zone by active and passive methods of MASW. The passive method of MASW has not been used previously on the territory of Russian Federation. In the passive method, geophones have been placed by “circle,” “square” and “triangle” layouts. Also, the special case of the passive method has been applied - passive roadside MASW. The telemetry system TELSS-3 has been used to register surface Rayleigh waves. The parameters of surveying system have been selected using the optimal recommended parameters and the reconnaissance surveys. Obtained seismograms have been processed using ParkSeis software. In the stage of dispersion analysis of MASW, the dispersion images have been obtained with clearly visible fundamental modes. The obtained dispersion curves have allowed making 2D profiles of shear-wave velocities for an active method and 1D profiles for passive methods of MASW. On the basis of these profiles the models of investigated soil stratification have been obtained. The presented results allow evaluating the effectiveness of the passive method of MASW as a tool for geotechnical investigations in cramped conditions, where deployment of surveying system for the active method is impossible.